A new currency for West African states: The theoretical and political conditions of its feasibility - Amato, Massimo; Nubukpo, Kako (PSL Quarterly Review, 2020)
Recent developments in the monetary situation in West Africa, in particular the transformation for the CFA franc area and the project to build a single currency for the CEDEAO/ECOWAS, require a systematic review of the assumptions underlying the formation of monetary unions. The article provides a critical review of the traditional theoretical foundations of optimal currency areas (OCAs) and their subsequent amendments, in light of the problems that emerged in the most relevant monetary unions. On specific points, a comparison is made between the eurozone and the CFA zone. The article then investigates the specific characteristics of the monetary area affected by the reform project, and finally it indicates the main lines along which the project of a common currency to all the states that currently make up the CEDEAO/ECOWAS could evolve, identifying four possible alternative roadmaps. JEL codes: F33, F53, F45